Analysis of Bitter Almonds and Processed Products Based on HPLC‐Fingerprints and Chemometry. Issue 3 (20th February 2023) - Zhang, Guoqin; Liu, Meiqi; Ma, Zicheng; Wang, Meng; Sun, Lili; Liu, Yanan; Ren, Xiaoliang
Abstract: In the processing field, there is a saying that "seed drugs be stir‐fried". Bitter almond (BA) is a kind of seed Chinese medicine. BA need be used after being fried. To distinguish raw bitter almonds (RBA) from processed products and prove the rationality of "seed drugs be stir‐fried", we analyzed the RBA and five processed products (scalded bitter almonds, fried bitter almonds, honey fried bitter almonds, bran fried bitter almonds, bitter almonds cream) using RP‐HPLC fingerprints and chemometric methods. The similarity between RBA and processed products was 0.733∼0.995. Hierarchically clustered heatmap was used to evaluate the changes in components. Principal component analysis (PCA) was used for classification, and all samples are distinguished according to RBA and five processing methods. Six chemical markers were obtained by partial least squares discriminant analysis (PLS‐DA). The content and degradation rate of amygdalin and β‐glucosidase activity were determined. Compared with RBA, the content and degradation rate of amygdalin, and β‐glucosidase activity were increased in bitter almonds cream. The content and degradation rate were decreased, and β‐glucosidase was inactivated in other processed products. The above results showed that stir‐frying had the best effect. The results showed that processing can ensure the stability of RBA quality, and the saying "seed drugs be stir‐fried" is reasonable. Abstract :